Antifungal effects of ethanolic and aqueous extracts of Vitex agnus-castus against vaginal isolates of Candida albicans - Nasser Keikha; Mahdieh Shafaghat; Seyed Mohamad Mousavi; Mahdiyeh Moudi; Farshid Keshavarzi (Mazandaran University of Medical Sciences, 2018)
Background and Purpose: Vulvovaginal candidiasis is one of the most common infections in female genital organs, which is caused by Candida species. Candida albicans is the causative agent of more than 80% of infections, and the role of non-Candida strains in the disease etiology is less prominent. The expansion of Azoles resistance among C. albicans strains is considered an important medical problem. According to previous studies, Vitex agnus-castus (vitex) has some antimicrobial effects. We aimed to evaluate the anti-fungal effects of aqueous and alcoholic extracts of vitex against clinical vaginal isolates of C. albicans in comparison with fluconazole. Materials and Methods: Gas chromatography-mass spectrometry analysis was performed on vitex to identify its possible bioactive components. Forty C. albicans clinical isolates were identified by using germ tube, chlamydospore production, culture on CHROMagar, and polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Finally, after the extraction of vitex, drug susceptibility test was carried out according to the clinical laboratory standards institute (CLSI) M27-S4 document guidelines. Results: The major chemical components of vitex leaf as determined by gas chromatography included α-Pinene, isoterpinolene, caryophyllene, and azulene. The minimum inhibitory concentrations (MICs) of aqueous and alcoholic extracts of vitex, as well as fluconazole were within the ranges of 15.62–62.5, 7.81–15.62, and 0.25–8 μg/mL, respectively. Conclusion: Our findings showed that the alcoholic and aqueous extracts of vitex had antifungal activity against clinical isolates of C. albicans. Moreover, the alcoholic extract of vitex and fluconazole were more effective against clinical vaginal isolates of C. albicans compared to the aqueous extract of vitex.